CLK2 in GABAergic neurons is critical in regulating energy balance and anxiety-like behavior in a gender-specific fashion - Norberto, Sónia; Assalin, Heloisa Balan; Guadagnini, Dioze; Tobar, Natália; Boer, Patrícia Aline; Kang, Min-Cheol; Saad, Mario Jose Abdalla; Kim, Young-Bum; Prada, Patricia Oliveira (Frontiers in Endocrinology, 2023)
Cdc2-like kinase (CLK2) is a member of CLK kinases expressed in hypothalamic neurons and is activated in response to refeeding, leptin, or insulin. Diet-induced obesity and leptin receptor-deficient db/db mice lack CLK2 signal in the hypothalamic neurons. The neurotransmitter γ-gamma aminobutyric acid (GABA), is among the most prevalent in the central nervous system (CNS), particularly in the hypothalamus. Given the abundance of GABA-expressing neurons and theirThis is a provisional file, not the final typeset article potential influence on regulating energy and behavioral homeostasis, Here we aimed to explore whether the deletion of CLK2 in GABAergic neurons alters energy homeostasis and behavioral and cognitive functions in both genders of mice lacking CLK2 in Vgat-expressing neurons (Vgat-Cre;Clk2 loxP/loxP ) on chow diet. We showed that deletion of CLK2 in GABAergic neurons increased adiposity and food intake in females. The mechanisms behind these effects were likely due, at least in part, to hypothalamic insulin resistance and upregulation of hypothalamic Npy and Agrp expression.Vgat-Cre; Clk2 loxP/loxP females were glucose intolerant, besides normal insulin and pyruvate sensitivity.Besides normal insulin and pyruvate sensitivity, Vgat-Cre; Clk2 loxP/loxP females were glucose intolerant. Male Vgat-Cre; Clk2 loxP/loxP mice showed an mild increase in food intake but a robust increased in energy expenditure (EE). Risen EE may account for avoiding weight and fat mass gain in male Vgat-Cre; Clk2 loxP/loxP mice. Vgat-Cre; Clk2 loxP/loxP mice had no alteration in cognition or memory functions in both genders. Interestingly, the deletion of deleting CLK2 in GABAergic neurons changed decreases anxiety-like behavior only in females, not males. These findings suggest that CLK2 in GABAergic neurons is critical in regulating energy balance and anxiety-like behavior in a genderspecific fashion and could be a molecular therapeutic target for combating obesity associated with psychological disorders in females.